"We Had a Beautiful Home . . . But I Think I'm Happier Here": A Good or Better Life in Residential Aged Care. (11th February 2015) - Minney, Melissa J.; Ranzijn, Rob
Abstract : Purpose of the Study: This qualitative study investigates residents' perspectives on whether a "good life" is possible for older people living in residential aged care (RAC) and offers insight into the services and support needed to sustain their good life. Design and Methods: Thirteen aged care residents (2 male, 11 female) ranging in age from 77 to 95 years, participated in semi-structured interviews in 2 RAC facilities in Adelaide, South Australia. Both facilities employed a model of aged care based on active aging and positive psychology principles called the partners in positive aging (PiPA) model. Results: Interpretative phenomenological analysis showed that residents' perception of a good life was centred on the service providers' ability to enhance their physical, social, and psychological well-being while allowing them to maintain their sense of identity. Counter-stereotypically, findings suggest that the aged care environment can provide older people who are physically frail but cognitively intact with a better life than when they were living in their own homes. Implications: Psychological good life theory needs to be adapted and modified when considering the needs of cognitively intact older adults in residential care.